Бухгалтерський облік фінансових результатів як передумова попередження банкрутства підприємства - Давидюк, Тетяна Вікторівна; Тарасова, О. В.; Ріпка, Л. М. (Харківський навчально-науковий інститут "Університет банківської справи", 2015)
В статті проаналізовано аналітичну інформацію щодо динаміки фінансового результату підприємств, визначено вплив факторів, що призводять до зниження платоспроможності вітчизняних підприємств, обґрунтовано необхідність своєчасності надання бухгалтерської інформації як передумови уникнення банкрутства підприємства.

This paper analyzes the analyzes of the dynamics of the financial results of enterprises, the influence of the factors leading to reduced solvency of domestic enterprises, the necessity of timeliness of financial information as a prerequisite to avoid bankruptcy. Amidst uncertain economic environment one gives much attentionto the bankruptcy issue because many domestic businesses are in crisis or bankruptcy. This is due to the financial failure of the company to overcome the economic crisis. The increasing number of bankrupt enterprises is influenced by most companies, which work with borrowed funds being insolvent and unable to fulfill their obligations not only to suppliers, but also to major creditors.
Accountang of financial results as a prerequise warning of bankruptcy
Keywords: банкрутство; економічна криза; фінансовий результат діяльності; бухгалтерський облік; фінансова звітність; bankruptcy; economic crisis; financial performance; accounting